Calcaneal bone status in elite karate practitioners - Imamura, H.; Oda, K.; Miyahara, K.; Matsuo, K.; Tai, K.; Yoshimura, Y.; Iide, K. (Journal of Athletic Enhancement, 2016)
Karate is one of the most popular martial arts practiced both inside and outside of Japan. Traditional karate training consists of the practice of basic techniques, kata and sparring. The basic techniques such as punching, kicking, blocking and striking are practiced either in the stationary position or with body movements in various formal stances. Kata are set forms in a pre-established sequence of defensive and offensive techniques and movements. Sparring is the execution of defensive and offensive techniques while one is freely moving against an opponent. In addition to the traditional karate training, many competitive practitioners cross train by undertaking strenuous running and weight training programs to increase endurance, muscle development and power.